2022
DOI: 10.1029/2021jd036197
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Charge Transfer During Long Continuing Currents in Natural Downward Flashes Using Single‐Station E‐Field Measurements

Abstract: The amount of charge transferred to ground during long continuing currents in natural downward flashes can be obtained either through direct current measurements or using remote electromagnetic fields, if direct measurements are not feasible. In this study, measurements of a single‐station E‐field antenna were used to estimate charge transfer during continuing currents. With time‐synchronized high‐speed video recordings serving as ground‐truth data for continuing current occurrence, we estimate transferred cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
(130 reference statements)
1
5
0
Order By: Relevance
“…(2014) for a flash with CC in New Mexico. Systematic differences in the total duration of the luminosity and the ELF radio signal of flashes with CC has been previously reported by several authors (e.g., Kohlmann et al., 2022; Saba et al., 2006). For example, Kohlmann et al.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…(2014) for a flash with CC in New Mexico. Systematic differences in the total duration of the luminosity and the ELF radio signal of flashes with CC has been previously reported by several authors (e.g., Kohlmann et al., 2022; Saba et al., 2006). For example, Kohlmann et al.…”
Section: Discussionsupporting
confidence: 57%
“…Zhang et al, 2016), which would allow for the ELF radio sensor to again detect it, as reported by Lapierre et al (2014) for a flash with CC in New Mexico. Systematic differences in the total duration of the luminosity and the ELF radio signal of flashes with CC has been previously reported by several authors (e.g., Kohlmann et al, 2022;Saba et al, 2006). For example, Kohlmann et al (2022) reported that the duration of the CC detected by the ELF radio sensor are between 10% and 69% shorter than in the videos.…”
Section: Role Of Flashes With CC In Igniting Lightning-induced Wildfiresmentioning
confidence: 61%
See 2 more Smart Citations
“…In numerous studies, a capacitive sensor, which consists of a sensing plate and a grounded one, had been utilized to estimate the transferred charge (Takeuti et al, 1978;Krehbiel et al, 1979;Brook et al, 1982;Qie X et al, 2000;Cui H et al, 2009;Saito et al, 2009;Zhang TL et al, 2009;Fan XP et al, 2014;Saito, 2016;Kohlmann et al, 2017Kohlmann et al, , 2022Haley et al, 2021). A capacitive sensor is designed to measure the electric field change to estimate the transferred charge quantitatively and investigate the charge structure inside a thundercloud.…”
Section: Introductionmentioning
confidence: 99%